Modeling and Electrical Characterization of CO₂/Ar Dielectric Barrier Discharges at Atmospheric Pressure - Mohamed Chenoui; Hocine Tebani; Djilali Benyoucef (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2026)
AbstractIn this study, a one-dimensional fluid model is employed to analyze the electrical and physicochemical properties of dielectric barrier discharges (DBDs) in pure CO₂ and CO₂/Ar mixtures at atmospheric pressure. Validation against experimental data confirms the accuracy of the model, especially for discharge current characteristics, with a peak current of 2.5 mA. Time-resolved analysis revealed that CO and O₂ represent the major species formed during CO₂ splitting, while O, O₃, and minor carbon-based species appear at lower concentrations. Charged species such as CO₂⁺ and CO₃⁻ were found to play a critical role in plasma kinetics, strongly correlating with current pulses during breakdown events. Parametric studies highlighted the influence of argon fraction, frequency, voltage, and pressure on discharge performance. Optimal CO production was obtained in CO₂/Ar mixtures with 75–90% Ar, at intermediate frequencies 3 kHz, moderate pressures 760 Torr, and applied voltages up to 9 kV. These findings provide valuable insights into plasma-assisted CO₂ conversion, emphasizing the importance of discharge conditions in enhancing efficiency and guiding the design of DBD reactors for sustainable carbon utilization. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).